A systematic literature review of Human Resource Information System (HRIS) usage in the health system of South Africa - Emmanuel Udekwe (Ümit Hacıoğlu, 2021)
This systematic literature review is aimed at determining the predominance of existing studies conducted in HRIS as it relates to HRM, HRH, workforce management and the use of Information Systems (IS) and technology within the health sector. The main findings of the study demonstrate that HRIS benefits are the most researched at 11.8% with a) impact: implementation and IS in healthcare:10.5%; b) effectiveness: motivation, competence, workforce IS and adoption: 9.2%; c) workforce retention and migration: 7.9% d) HRIS and EHRM for decisions 5.3%, e) HRIS in HRM and digital records 2.6%; f) IT in the healthcare setting standing at 1.3%.